Accelerometer Sensor Applications Early Warning System Train Accidents due to Landslide at Laboratory Scale. (March 2017) - Alimuddin,; Sulaiman, F; Parinduri, I H; Abdullah, R; Firmansyah, T; Syarif, M S
Abstract: Railway is a means of transportation that is favoured by the people. Accidents often occur in provinces Jawan West, Central Java, East Java and Banten. The cause of the accident because of the location of heavy rain and soil in the landslide. The purpose of this study was to design an early warning accelerometer sensor on the railway line and test validation early warning accelerometer sensor on the railway. Methods real-time create an early warning system for landslides that is easy to use and effective in detecting landslide, using sensors and microcontrollers accelometer arduino. It can be concluded that the early warning system (early warning system) works digitally, real-time, and effective response to the reading of less than 1 second, the average error of the accelerometer sensor reading is 0 to 3.84%.